The Effects of Banana Blossom (Musa Acuminate Colla) Consumption on Increased Breast Milk Production in the Work Area of Talaga Jaya - Masmuni Wahda Aisya; Fatmah Zakaria; Wirna Daud (Journal La Lifesci, 2020)
Breast Milk (ASI) is the best food for babies, in increasing milk production, breastfeeding mothers are advised to consume banana bud because it contains lactagogum compounds that can increase milk production, especially in mothers who experience milk production problems. This research aims to determine the effect of Banana Blossom consumption on increasing milk production in the work area of ​​Talaga Jaya Health Center. The design was Quasi Experimental with Pre-post Nonequivalent Control Group Design. The population in this study were all breastfeeding mothers in the working area of ​​Talaga Jaya Health Center totaling 122 people. The sample in this research used purposive non-probability sampling with purposive sampling technique with an observation sheet as data collection technique. The data were analyzed using Wilcoxon Signed Rank Test to see differences in the frequency of breast milk production before and after consumption of the Banana Blossom while the Chi Square test is there to see the effect of Banana Blossom consumption on breast milk production with a P value <0.05. The results showed there was a significant effect on increasing milk production in nursing mothers with a p-value of 0.002 <0.05.